A reappraisal of the Border Cave 1 cranium (KwaZulu-Natal, South Africa). (15th April 2022) - Beaudet, Amélie; Francesco d'Errico,; Backwell, Lucinda; Wadley, Lyn; Zipfel, Bernhard; de la Peña, Paloma; Reyes-Centeno, Hugo
Abstract: Besides providing a unique archaeological assemblage that documents the early emergence of complex behaviour in the human lineage, Border Cave (South Africa) is noteworthy for having yielded hominin remains of at least nine individuals, including the partial cranium Border Cave 1. While the exact provenance of Border Cave 1 is unknown, sequence stratigraphy and ESR dating converge towards an age from about 82 ka to 170 ka. Here we present novel information about the brain, braincase and bony labyrinth of Border Cave 1 and discuss related evolutionary implications. We compare Border Cave 1 to specimens of Early and Middle Pleistocene Homo as well as to fossil and extant Homo sapiens . Virtual segmentation techniques were used to reconstruct the brain and bony labyrinth endocasts, assess the distribution of cranial bone thickness, and identify the vascular and sulcal imprints preserved on the inner surface of the braincase. Our results show that the overall morphology of the brain endocast approximates the globular shape of the modern human brain and differs from the long and low brains seen in Middle Pleistocene fossil hominins. The vascular imprints preserved on the right hemisphere indicate that the middle branch derives from the anterior branch, which is a pattern shared with Neanderthals and modern humans. Bone thickness distribution in the Border Cave 1 cranium resembles the patterns seen in Cro-Magnon 1 and Abri Pataud 1, which both share a diffuse distribution of thickened areas over the frontal region. Finally, the relative size and curvature of the semicircular canals of the bony labyrinth conform to the ancestral configuration shared between Early and Late Pleistocene fossil hominins from Africa and the Levant, as well as modern humans, and distinct from the more derived condition documented within Neanderthals. We discuss the implications of our findings for understanding the biogeography, evolution, and, to some extent, behaviour of fossil Homo sapiens . Highlights: Border Cave 1 cranium, found in 1940–42, comes from alleged MSA deposits. In this paper we present a computer-assisted reappraisal of the Border Cave 1 cranium. The brain endocast has a globular shape similar to extant humans. Bone thickness distribution resembles that of Late Pleistocene fossil hominins. The semi-circular canals show an ancestral configuration as compared to the derived condition seen in Neanderthals.